Narrating Narcos : Culiacán and Medellín - Polit Dueñas, Gabriela (Book collections on Project MUSE., 2013)
Narrating Narcos presents a probing examination of the prominent role of narcotics trafficking in contemporary Latin American cultural production. In her study, Gabriela Polit Dueñas juxtaposes two infamous narco regions, Culiacán, Mexico, and Medellín, Colombia, to demonstrate the powerful forces of violence, corruption, and avarice and their influence over locally based cultural texts. Polit Dueñas provides a theoretical basis for her methods, citing the work of Walter Benjamin, Pierre Bourdieu, and other cultural analysts. She supplements this with extensive ethnographic fieldwork, interview.